2006
DOI: 10.1080/00365510600564949
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor serum concentrations in hypercholesterolemic patients

Abstract: A relationship was found between serum levels of VEGF and most atherogenic lipoproteins. In patients with hypercholesterolemia treated with pravastatin, a reduction in VEGF and CRP was seen in addition to lipid decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…52 Moreover, pDC depletion reduced vascular endothelium growth factor a potent angiogenic factor involved in vascular permeability, 53 the concentration of which increases in both serum and plaques during atherosclerosis. 39,40 Despite the cytokine-mediated effects of pDCs, through the release of IFN-α, having been implicated in a pathogenic T-cell response in human atherosclerotic plaques, 26 IFN-α was below the level of detection in both aortic tissue and serum samples in our apoE −/− mice irrespective of pDC depletion. This suggests that large increases in IFN-α production are not responsible for the pDC-mediated atherogenic effect in our experimental settings, although it is possible there are minor localized increases in expression, which the immunoassay could not detect.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…52 Moreover, pDC depletion reduced vascular endothelium growth factor a potent angiogenic factor involved in vascular permeability, 53 the concentration of which increases in both serum and plaques during atherosclerosis. 39,40 Despite the cytokine-mediated effects of pDCs, through the release of IFN-α, having been implicated in a pathogenic T-cell response in human atherosclerotic plaques, 26 IFN-α was below the level of detection in both aortic tissue and serum samples in our apoE −/− mice irrespective of pDC depletion. This suggests that large increases in IFN-α production are not responsible for the pDC-mediated atherogenic effect in our experimental settings, although it is possible there are minor localized increases in expression, which the immunoassay could not detect.…”
Section: Discussionmentioning
confidence: 74%
“…We observed a >90% (P<0.05) decrease in IL-12, a proatherogenic cytokine in pDC-depleted mice in addition to decreases in the proatherogenic chemokines: KC (chemokine [C-X-C motif] ligand [CXCL] 1), monokine induced by IFN-γ/CXCL9, and IFN-γ−induced protein 10/CXCL10. Vascular endothelium growth factor, the concentration of which increases in both serum and plaques during atherosclerosis, 39,40 was found to be reduced by 75% (P<0.05) in pDC-depleted mice. Concentrations of fibroblast growth factor-basic, granulocyte-macrophage colony-stimulating factor, IFN-γ, IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IL-13, IL-17, monocyte chemoattractant protein-1, macrophage inflammatory protein-1α, and TNF-α did not differ significantly between groups or were below the level of detection (data not shown).…”
Section: Pdc Depletion Results In Systemic Reductions In Proatherosclmentioning
confidence: 90%
“…Studies have shown a correlation between VEGF serum levels and the concentrations of cholesterol and triglycerides [29, 30], with high triglycerides and cholesterol associated with elevated VEGF, presumably due to endothelial damage. Therefore, we sought to determine whether lipid profiles differed in patients with high or low serum VEGF.…”
Section: Resultsmentioning
confidence: 99%
“…There is a relationship between hypercholesterolemia and serum level of VEGF31. The endothelial replication necessary for vascular growth is markedly impaired in the presence of hypercholesterolemia32.…”
Section: Introductionmentioning
confidence: 99%